A Novel Technology for Hematopoietic Stem Cell Expansion Using Combination of Nanofiber and Growth Factors - Lu, Jingwei; Aggarwal, Reeva; J. Pompili, Vincent; Das, Hiranmoy (Recent Patents on Nanotechnology, 2010)
Hematopoietic stem cell transplantation has been applied as a standard procedure of treatment for hematological disorders like multiple myeloma and leukemia for several decades. Various sources of stem cells like bone marrow, peripheral blood and umbilical cord blood are used for the transplantation. Among these umbilical cord blood is currently preferred due to the primitiveness of the derived stem cells and minimal possibilities of graft versus host disease or development of graft induced tumors. One of the problems for these sources is the procurement of sufficient number of donor stem cells. Inadequate number of cells may lead to delayed recovery and decrease survivability of the patient. Thus to overcome the limitation of stem cell number, development of an ex-vivo expansion technology is critically important. The recent emerging technology using nanofiber in combination with growth factors has made a significant improvement to the field of regenerative medicine and a couple of patents have been filed. In this review, we will focus on factors regulating hematopoietic stem cell self-renewal and expansion emphasizing on nanofiber as a supporting matrix.
Keywords: cytokines